Pengembangan Model Pembelajaran IPA SD Berbasis Bahan Di Lingkungan Sekitar Melalui Pendekatan Starter Eksperimen - Muharram --; Hamka Lodang; Nurhayati --; Munir Tanrere (Jurnal Pendidikan dan Kebudayaan, 2010)
This study is a research and development that was conducted through four steps and is mentioned as a â€œFour-D Modelâ€, namely define, design, develop and disseminate. The aim of this research is to produce instructional model, that is a starter experiment based on environmental materials and supporting of instructional model, including: experiment guidance, student worksheet and instrument ofÂ evaluation. The product of this research is the syntax of instructional model that consist of six steps and supporting of the model, namely three supplement books for Elementary School. The titles of the books are â€œScience Skillâ€ for 4th, 5th, and 6th Gradeâ€. The instructional model and its supporting were validated by expertâ€™s team and they were categorized in valid that are 88.40% for instructional model and 84.66% for the supporting of the instructional model. Try out result that conducted through the pre-experiment results showed that: 1) the instructional model and its supporting could be used by both the teacher and the student; 2) Apply the model and its supporting increase the activity, interest, scientific attitude, skill of science process, and the studentâ€™s achievement.Â ABSTRAKPenelitian ini termasuk jenis penelitian pengembangan (Research and Development) yang dilakukan melalui empat tahap yang dikenal dengan â€œFour-D Modelâ€ yaitu define, design, develop, and disseminate. Penelitian ini bertujuan untuk menghasilkan model pembelajaran berbasis bahan-bahan di lingkungan sekitar serta perangkat pembelajaran yang meliputi, Panduan Eksperimen, Lembar Kerja Siswa, dan Alat Evaluasi. Luaran penelitian adalah sintaks model pembelajaran 6 langkah dan perangkat pembelajaran berupa tiga buah buku suplemen IPA SD dengan judul â€œTerampil Sainsâ€ untuk kelas 4, 5, dan 6. Hasil validasi model dan perangkat pembelajaran oleh tim akhli menunjukkan bahwa model dan perangkat pembelajaran termasuk katagori valid dengan persentasi validitas masing-masing: 88,40% dan 84,66%. Hasil ujicoba melalui penelitian pra eksperimen menunjukkan bahwa: 1) model dan perangkat pembelajaran digunakan dengan baik oleh guru dan siswa; 2) penerapan model pembelajaran akan meningkatkan aktivitas, minat dan sikap ilmiah, keterampilan proses sains, dan hasil belajar siswa.